cerebellar infarction in a 9 years old child presenting with fever and ataxia - vafaeeshahi, Dr; Azizi Shalbaf, Nazanin; Tahernia, Leila (Iranian Journal of Child Neurology, 2019)
Background: Cerebellar acute ischemic stroke (AIS) can be a complication of minor head trauma, vertebral artery dissection, vasospasm or systemic hypoperfusion. Computed Tomography (CT) scan usually is negative few hours after acute infarction. Magnetic resonance imaging (MRI) is superior to CT scan for posterior fossa lesions and also in acute phase of cerebellar stroke specially in children. Case summary: The patient was a 9 years Old girl presenting with sudden onset of headache and recurrent vomiting, ataxia and history of 3 consecutive days of fever and malaise. In the report of MRI there were abnormal low T1 and high T2 signal intensity in left cerebellar hemisphere involving superior and middle cerebellar peduncles. After 4 days of admission, the patient became drowsy, symptoms progressed and transfered to the pediatric intensive care unit (PICU). The patient underwent hemispherectomy surgery of the left cerebellar hemisphere because of acute obstructive hydrocephaly. After 5 months of occupational therapy the force of her extremities were normal and the ataxia completely disappeared. Conclusion: Childhood acute ischemic stroke although rare can happen with cerebellar involvement. Because in our patient the first brain CT scan was nearly normal and a false negative rate for initial computed tomography (CT) scanning of 60-80 percent also contributes to missed and delayed diagnosis of childhood AIS, we conclude that for every child presenting with acute ataxia without identified cause in addition to CT scan, MRI also being ordered and from the beginning beside other causes, stroke be contemplated as a cause of ataxia.